Increased Serum Resistance in Klebsiella pneumoniae Strains Producing Extended-Spectrum β-Lactamases - Sahly, H. (American Society for Microbiology, 2004)
The aim of this study was to determine whether there is an association between serum resistance, O serotypes, and the production of extended-spectrum β-lactamases (ESBLs) in Klebsiella pneumoniae. Ninety ESBL-producing and 178 non-ESBL-producing K. pneumoniae isolates gathered in five European countries were O serotyped and tested for sensitivity to the serum's bactericidal effect. The frequency of serum-resistant isolates was higher among ESBL-producing strains (30%; 27/90 isolates) than among non-ESBL-producing strains (17.9%; 32/178 isolates) (P = 0.037; odds ratio [OR] = 1.96; 95% confidence interval [95% CI] = 1.08 to 3.53). Although O1 was the most common O serotype in both Klebsiella groups, its frequency among ESBL-producing strains was significantly higher (59%; 53/90 isolates) than among non-ESBL producers (36%; 64/178 isolates) (P = 0.0006; OR = 2.5; 95% CI = 1.52 to 4.29). Furthermore, the prevalence of the O1 serotype was higher among serum-resistant strains of both ESBL-producing (74%; 20/27isolates) and non-ESBL producers (75%; 24/32 isolates) than among serum-sensitive ESBL producers (52.4%; 33/63 isolates) and non-ESBL producers (27.4%; 40/146 isolates). Serum resistance among ESBL-producing strains (36%; 17/47 isolates) versus non-ESBL-producing strains (16%; 27/166 isolates) was also significantly higher after the exclusion of clonal strains (P = 0.0056; OR = 2.9; 95% CI = 1.41 to 6.01). Sixteen ESBL types were detected, among which the frequency of serum resistance was significantly lower among the SHV-producing strains (9/48 isolates) than among the TEM producers (16/35 isolates) (P = 0.016; OR = 3.65; CI = 1.3 to 9.7). Curing ESBL-coding plasmids did not influence the serum resistance of the bacteria; all six plasmid-cured derivatives maintained serum resistance. The present findings suggest that ESBL-producing strains have a greater pathogenic potential than non-ESBL-producing strains, but the linkage between O serotypes, serum resistance, and ESBL production remains unclear at this stage.